(untitled) (Sains Humanika, 2015)
While a growing body of empirical research has indicated that employee’s perception regarding human resources management practices play significant role in explaining turnover intention, however, the mechanism behind this relationship remains unclear. This study investigated the mediating effect of organisational trust on training and development - turnover intention relationship as well as the relationship between compensation practices and turnover intention. Data were collected from 175 Registered Nurses in Nigerian public hospitals. Using bootstrap resampling technique for testing an indirect effect, training and development and compensation practices were found to be the antecedents of organisational trust, which in turn mediates their relationships with employee’s turnover intention. The theoretical and practical implications of the results have been discussed.